Magnetic excitations beyond the single- and double-magnons - Elnaggar, Hebatalla; Nag, Abhishek; Haverkort, Maurits W.; Garcia-Fernandez, Mirian; Walters, Andrew; Wang, Ru-Pan; Zhou, Ke-Jin; de Groot, Frank (Nature Communications, 2023)
A photon carrying one unit of angular momentum can change the spin angular momentum of a magnetic system with one unit (ΔMs = ±1) at most. This implies that a two-photon scattering process can manipulate the spin angular momentum of the magnetic system with a maximum of two units. Herein we describe a triple-magnon excitation in α-Fe2O3, which contradicts this conventional wisdom that only 1- and 2-magnon excitations are possible in a resonant inelastic X-ray scattering experiment. We observe an excitation at exactly three times the magnon energy, along with additional excitations at four and five times the magnon energy, suggesting quadruple and quintuple-magnons as well. Guided by theoretical calculations, we reveal how a two-photon scattering process can create exotic higher-rank magnons and the relevance of these quasiparticles for magnon-based applications.
Gesehen am 25.09.2023